从沈从文的小说《丈夫》到黄蜀芹的电影《村妓》= From Shen Cong-wen’s short story "The Husband" to Huang Shu-qin’s film "Mainland Prostitute" - 邱姝敏 Ku, Shu Min (2012)
1994年，沈从文的短篇小说《丈夫》由女性导演黄蜀芹改编为电影《村妓》。在改编的过程中，黄蜀芹调整了文本的内容，也从不同的视角呈现这部电影。沈从文的小说叙述一个由乡下来的丈夫探望在城里当船妓的妻子，以及他所面临的种种尴尬情况。与之相对的，电影则比较关注其妻子所面对的困境。本论文将从小说和电影这两种不同媒介的呈现方式入手，分析其中的差异。对《丈夫》和《村妓》的内容进行对比，分析探讨电影中场景的置入，角色的增加及取材自沈从文其他小说的内容添补。接着分析《村妓》当中的性别叙事：三个不同年龄层的女性角色如何呈现出小说以外的故事——概括湘西船妓一生的命运。最后，本文也将指出“妻子”一角在影片当中自主形象的虚幻性，并为《村妓》的改编成就做出总结。A short story “The husband” written by Shen Cong-Wen was adapted to the film “Mainland Prostitute” by Huang Shu-qin in year 1994. During the making of the film, Huang Shu-qin had changed the content and narrative standpoint of the story. The original story of “The husband” narrates the embarrassing situations faced by a rural man while visiting his wife, who worked as a ship prostitute in the city. In contrast, the main focus of the film“Mainland Prostitute”are the dilemmas of the wife. The main objective of this reserach projected is to analyse the differences between the original story and the film, by comparing the content of “The husband”and “Mainland Prostitute”. Scenes interpolation, characters invention, and the incidents of quotes to added to the film. In addition, there was a discussion regarding how a hidden story of a prostitute’s life from young to old were narrated through three female characters. Finally, this article point out the illusion of indepentdent characteristic of the wife, and make a conclusion for the whole thesis.